2018
DOI: 10.1016/j.clbc.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aromatase Inhibitor Therapy on Sleep and Activity Patterns in Early-stage Breast Cancer

Abstract: Daytime function decreased after initiation of AI therapy and correlated moderately with increased fatigue, although no association was identified with changes in pain or sleep quality. Additional studies are required to understand why function is reduced, which could have implications for interventions to improve patient tolerance of, and persistence with, AI therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
6
0
3
Order By: Relevance
“…This finding is consistent with the literature, confirming the relatively high proportion of breast cancer patients suffering from sleep disorders compared to the general cancer patients’ population [ 3 , 36 , 40 ]. However, there was no worsening of sleep disturbances during the administration of AIs and this finding is similar to the results of a recently published study [ 41 ]. As mentioned previously, insomnia often clusters with anxiety and depression and consequently both parameters evaluated by the HADS score did not change after the introduction of AIs in these patients.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with the literature, confirming the relatively high proportion of breast cancer patients suffering from sleep disorders compared to the general cancer patients’ population [ 3 , 36 , 40 ]. However, there was no worsening of sleep disturbances during the administration of AIs and this finding is similar to the results of a recently published study [ 41 ]. As mentioned previously, insomnia often clusters with anxiety and depression and consequently both parameters evaluated by the HADS score did not change after the introduction of AIs in these patients.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to energy intake and physical activity, sleep patterns are now recognized as profoundly influencing metabolic health and are known to be regulated by sex steroids (Brockman et al, 2011). Importantly, aromatase inhibition therapy in humans is known to cause insomnia (Bhave et al, 2018;Karatas et al, 2015), but the mechanisms are not fully understood. We assessed sleep patterns in the ArKO and WT mice and found that ArKO females slept more during the dark cycle (i.e., when mice are most typically active) and light (i.e., typical sleep/ inactive) cycle relative to WT.…”
Section: Discussionmentioning
confidence: 99%
“…Une revue de littérature publiée en 2015 [57] rapportait cependant que la chimiothérapie pourrait accentuer des difficultés de sommeil déjà présentes avant l'initiation des traitements dans le cancer du sein. À notre connaissance, seules deux études se sont intéressées aux effets de l'hormonothérapie (anti-aromatase) [58] et de la radiothérapie [59] sur les paramètres de sommeil mesurés en actimétrie dans le cancer du sein. Les résultats ne montrent pas de modification de l'efficacité du sommeil, du temps total de sommeil, ni des éveils nocturnes après l'initiation du traitement par hormonothérapie [58].…”
Section: Evaluation Du Sommeilunclassified
“…À notre connaissance, seules deux études se sont intéressées aux effets de l'hormonothérapie (anti-aromatase) [58] et de la radiothérapie [59] sur les paramètres de sommeil mesurés en actimétrie dans le cancer du sein. Les résultats ne montrent pas de modification de l'efficacité du sommeil, du temps total de sommeil, ni des éveils nocturnes après l'initiation du traitement par hormonothérapie [58]. Concernant les effets de la radiothérapie, les résultats montrent que près de la moitié des patientes avaient un temps d'éveil et un temps total de sommeil hors des valeurs normées [59].…”
Section: Evaluation Du Sommeilunclassified
See 1 more Smart Citation